Autologous Morselised Bone Grafting for Medial Tibial Defects in Total Knee Arthroplasty. (August 2015) - Sugita, Takehiko; Aizawa, Toshimi; Sasaki, Akira; Miyatake, Naohisa; Fujisawa, Hirokazu; Kamimura, Masayuki
Purpose: To evaluate the outcome of autologous morselised bone grafting for a medial tibial defect of ≥10 mm deep in 45 total knee arthroplasties (TKAs). Methods: 38 patients aged 46 to 85 (mean, 73) years underwent 45 TKAs and autologous morselised bone grafting for a medial tibial defect of ≥10 (range, 10–25) mm in depth by a single surgeon. In the first 19 TKAs, 2 resected subchondral bone plates from the lateral tibial plateau were driven into 2 gutters made on the floor of the medial tibial defect as bony support posts. Morselised cancellous bone grafts were then impacted around these posts. In the remaining 26 TKAs, multiple drill holes were made on the floor of the defect to decrease the remodelling time. Morselised cancellous bone grafts were impacted to fill the defects. The tibial components were fixed with cemented (n=34) or non-cemented (n=11) technique. Internal fixation devices were not used; stem extension was used in only 2 TKAs (in a patient with Charcot joint and a patient undergoing revision TKA). Results: After a mean follow-up duration of 65 (range, 24–174) months, no patient showed gait disturbance. The mean knee flexion angle was 113.8° (range, 90°–130°). No absorption or collapse of the grafted bone, or component loosening were noted on radiographs. The grafted bone completely incorporated into the host bone, with bony trabeculae crossing the interface within 2 years in the first 19 TKAs and within one year in the latter 26 TKAs. The margin of the grafted area resembled bony cortex in 30 TKAs. Conclusion: Autologous morselised bone grafting is a viable option for most medial tibial defects during TKA.